Assessing the Post-Disaster Effects of COVID-19 Pandemic Towards Malaysian Construction Industry - Ting, Sim Nee; Ang, Chern Xing; Lee, Yee Yong (Penerbit Universiti Sains Malaysia, 2024)
Amidst the global upheaval caused by the Coronavirus 2019 (COVID-19) pandemic, substantial disruptions reverberated across nations, including Malaysia, prompting extensive lockdown measures. In response to the virus’s transmission, the Malaysian government enforced the Movement Control Order (MCO) starting on the 18th March 2020. This directive wielded a profound influence, notably impacting diverse sectors within Malaysia, including the construction industry. This study aimed to assess the effects of the COVID-19 pandemic as a post-disaster scenario, with the construction sector as the focal point. The study is executed within the framework of two primary parameters: the occurrence and the significance of the ramifications from the pandemic. A quantitative research methodology was employed, wherein a questionnaire survey was distributed to active industry participants in the construction industry in East and West Malaysia. In total, 197 responses were collected and analysed using the relative importance index technique. Across nine construction domains, 49 effects were investigated. Findings show that the scarcity of materials and workforce, followed by the shortage of labour force especially foreign labour, construction delays stemming from restrictive mandates, revisions in scheduling and work scope and an escalation in material costs are among the top five rankings of the post COVID-19 effects on the construction industry. The outcomes of this research have substantially contributed to the comprehension of the effects induced by the COVID-19 pandemic on the construction industry. The main aim is to amass data that can be leveraged by policy makers to bolster post-disaster management strategies within Malaysia, thereby facilitating the transfer of knowledge for future post disaster management endeavours. Additionally, the study has shed light on the disparities delineated along the regional demarcation of East and West Malaysia.